Monotony in the consumption of fruits and vegetables and food environment characteristics - Raquel de Deus Mendonça; Mariana Souza Lopes; Patrícia Pinheiro Freitas; Suellen Fabiane Campos; Mariana Carvalho de Menezes; Aline Cristine Souza Lopes
ABSTRACT OBJECTIVE To analyze the quantity and diversity in the consumption fruits and vegetables, as well as its relationship with the consumer's purchase characteristics and food environment. METHODS Baseline study stemming from a controlled and randomized community trial investigating a sample representative of Primary Health Care services (Health Academy Program) of Belo Horizonte, state of Minas Gerais. The intake of fruits and vegetables was analyzed in servings/day, whereas diversity was assessed by the Food Frequency Questionnaire. Users were also questioned on the frequency, purchase location and availability of these foods at their households. To assess the consumer's food environment, commercial establishments within a 1.6 km radius around the program unit sampled were audited. RESULTS 3,414 adults and older adults (88.1% women) were investigated, as well as 336 commercial establishments, in 18 units of the Health Academy Program. The average consumption of fruits and vegetables was adequate [5.4 (SD = 2.1) servings/day] but monotonous, with average daily intake of two different types. In the establishments audited, a good diversity (77.7% and 85.0%) and variety (74.5% and 81.4%) of fruits and vegetables was observed, although with lower quality of vegetables (60.4%). After adjusting for sociodemographic variables, we identified that knowledge on food crops (p = 0.006), increased monthly availability of fruits at households (p < 0.001), and greater variety of fruits (p = 0.03) and quality of vegetables (p = 0.05) in commercial establishments could improve the quantitative intake of fruits and vegetables, whereas a greater variety of fruits (p = 0.008) would increase consumption diversity. CONCLUSIONS The intake of fruits and vegetables was quantitatively adequate but monotonous, being influences by the consumer environment. Such results highlight the need for improving educational actions in health services and programs, in addition to acting on the consumer environment, aiming to promote and maintain the adequate and diversified consumption, as recommended by Brazilian guidelines for proper and healthy eating.